Kekerasan Bermotif Agama: Perspektif Fundamentalisme, Radikalisme, dan Ekstremisme - Nuraeni, Heni Ani; Salsabila, Salsabila; Dapfa, Agam Muhammad; Wardani, Reny Sukma (Jurnal Ilmiah Wahana Pendidikan, 2024)
Instead of viewing violence through the tired lens of "fundamentalism" and "radicalism," this paper will take a deep dive into history, seeking the true roots of such acts draped in religious garb. Armed with historical-critical analysis, it aims to illuminate a new paradigm for understanding these complexities.Western perspectives often paint these terms as a dark tapestry of outdated extremes, rigid conservatism, and even violent tendencies. But applying such labels to entire communities, particularly Muslims, proves far too simplistic. This paper argues that attributing these labels ignores the intricate reality of socio-political grievances that can fuel violence, even while actors wave religious banners. The historical and sociological lens reveals a picture far more nuanced than mere religious extremism. It exposes the underlying currents of power struggles and social discontent that can distort faith into a tool for violence. To label these acts purely as "religious" risks obscuring the true forces at play and hindering effective solutions. Instead of simplistic labels, this paper seeks to uncover the complex tapestry of factors that lead to violence, even when cloaked in religious language. By understanding the historical and socio-political roots of these issues, we can move beyond harmful generalizations and work towards a more informed and compassionate approach to addressing them.